2009
DOI: 10.1099/mic.0.028852-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth of calcium-blind mutants of Yersinia pestis at 37 °C in permissive Ca2+-deficient environments

Abstract: Cells of wild-type Yersinia pestis exhibit a low-calcium response (LCR) defined as bacteriostasis with expression of a pCD-encoded type III secretion system (T3SS) during cultivation at 37 °C without added Ca2+ versus vegetative growth with downregulation of the T3SS with Ca2+ (≥2.5 mM). Bacteriostasis is known to reflect cumulative toxicity of Na+, l-glutamic acid and culture pH; control of these variables enables full-scale growth (‘rescue’) in the absence of Ca2+. Several T3SS regulatory proteins modulate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
(57 reference statements)
0
19
0
Order By: Relevance
“…It might be concerned with defective proton motive force generation, reduced ATP pools, and the inability to export toxic levels of Na ϩ from the cytoplasm (64,67,68). At 37°C Yersinia appears to be sensitive to Na ϩ but only during active T3S; the presence of Ca 2ϩ in the growth medium inhibits Ysc-Yop T3S, concomitantly relieving Na ϩ sensitivity and reinitiating growth (69). It follows that the Na ϩ and temperature sensitivity displayed by a yopD null mutant constitutively producing an active T3SS cannot be suppressed by the addition of Ca 2ϩ (a so-called Ca 2ϩ blind phenotype) (69).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It might be concerned with defective proton motive force generation, reduced ATP pools, and the inability to export toxic levels of Na ϩ from the cytoplasm (64,67,68). At 37°C Yersinia appears to be sensitive to Na ϩ but only during active T3S; the presence of Ca 2ϩ in the growth medium inhibits Ysc-Yop T3S, concomitantly relieving Na ϩ sensitivity and reinitiating growth (69). It follows that the Na ϩ and temperature sensitivity displayed by a yopD null mutant constitutively producing an active T3SS cannot be suppressed by the addition of Ca 2ϩ (a so-called Ca 2ϩ blind phenotype) (69).…”
Section: Discussionmentioning
confidence: 99%
“…At 37°C Yersinia appears to be sensitive to Na ϩ but only during active T3S; the presence of Ca 2ϩ in the growth medium inhibits Ysc-Yop T3S, concomitantly relieving Na ϩ sensitivity and reinitiating growth (69). It follows that the Na ϩ and temperature sensitivity displayed by a yopD null mutant constitutively producing an active T3SS cannot be suppressed by the addition of Ca 2ϩ (a so-called Ca 2ϩ blind phenotype) (69). This led to a proposal that another component of the Ysc-Yop T3SS may facilitate the elevation of toxic Na ϩ levels inside the bacteria, thus inhibiting a fundamental cellular process needed for vegetative growth (64,69).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, consecutive passages at 37°C in the absence of Ca 2+ results in loss of the pCD1 plasmid, which encodes the T3SS, and attenuation in mice [336,337]. To date, there is little known about the biological relevance for the LCR [1,[338][339][340][341]. Szatmari and colleagues recently demonstrated that Rab11b interacts with Hook, a negative regulator of endosome maturation, to facilitate crosstalk between recycling endosomes and induction of autophagy [254].…”
Section: Potential Biological Impact Of Y Pestis Low Calcium Responsmentioning
confidence: 99%